Antiphospholipid Syndrome Manifesting as Myocardial Infarction: A Case Report and Review of the Literature - Shahi, Shayan; Nematollahi, Soroush; Mohammadi, Amirali; Aghajani, Hassan (The Indonesian Heart Association, 2025)
Background: Antiphospholipid syndrome (APS) is characterized by the presence of antiphospholipid antibodies, including lupus anticoagulant, anticardiolipin antibodies, and β2-glycoprotein I. These antibodies target phospholipids and associated proteins, leading to diverse clinical manifestations such as stroke, myocardial infarction, and deep vein thrombosis. Acute myocardial infarction caused by arterial thromboembolism is a rare first manifestation of APS. Case summary: We present a case study of a 37-year-old female with a suspicious history of Deep Vein Thrombosis (DVT) with no identifiable risk factors a decade ago and recently suffered a sudden Myocardial Infarction (MI) due to arterial Thrombosis. Angiographic appearance and Angioplasty were challenging at the presentation time since the clot was migratory and moved between coronary vessels. We conducted a Thrombophilia evaluation due to the unusual site of Thrombosis and the patient's age at the presentation, which led us to establish the diagnosis of antiphospholipid syndrome (APS) Brief conclusion: Different anticoagulation regimes are suggested depending on whether an APS patient has an arterial or venous thrombosis. According to the clinical situations, there may be potential therapeutic challenges. Patients with APS are required to maintain lifelong oral anticoagulation with vitamin K antagonists. Meanwhile, Non-vitamin K Oral Anticoagulants (NOACs) are under investigation as potential future treatments for APS.